Protein levels in enteral feeds: do these meet requirements in children with severe cerebral palsy? - Schoendorfer, N.; Tinggi, U.; Sharp, N.; Boyd, Roslyn; Vitetta, L.; Davies, P. (2012)
Children with cerebral palsy (CP) have been documented to have feeding difficulties, which increase in line with condition severity and result in lowered growth potential. Much nutrition literature surrounds energy intake and expenditure in these children, with less information available on other parameters such as protein and micronutrients, which are also important for growth and development. We examined differences in protein intake and a variety of protein metabolism indices in children with CP compared with controls. A total of twenty-four children aged 4-12 years with marked CP fed orally (O, n 15) or enterally (E, n 9) were recruited, including age-matched typically developing children (C, n 24). Fasting blood samples were analysed for levels of albumin, creatinine, urea and urate. Parents collected an exact food replica for three consecutive days of their child's actual intake, which were directly analysed for protein content. Significant differences were found in protein intakes between the groups (mean percentage minimum requirements: E = 178 (sd 47); O = 208 (sd 95); C = 311 (sd 119), P = 0·005). Despite all children consuming over recommended levels, children with CP had significantly reduced levels of the protein metabolic indices compared with controls. These include as z-scores: albumin mean C = 0·71 (sd 1·04) and CP = - 0·17 (sd 1·60), P = 0·03; creatinine C = - 2·06 (sd 0·46) and CP = - 3·11 (sd 0·98), P < 0·001; urate C = 0·18 (sd 0·62) and CP = - 0·58 (sd 0·93), P = 0·002. Post hoc analysis, the present data show potentially greater protein metabolism issues in enterally fed children, compared with the other groups. This may also support recent literature that suggests shortfalls in current recommendations.